Sand transverse dune aerodynamics: 3D coherent flow structures from a computational study. Issue 147 (December 2015) - Bruno, Luca; Fransos, Davide
Abstract: The engineering interest about dune fields is dictated by their interaction with a number of human infrastructures in arid environments. Sand dunes dynamics is dictated by wind and its ability to induce sand erosion, transport and deposition. A deep understanding of dune aerodynamics serves then to ground effective strategies for the protection of human infrastructures from sand, the so-called sand mitigation. Because of their simple geometry and their frequent occurrence in desert area, transverse sand dunes are usually adopted in the literature as a benchmark to investigate dune aerodynamics by means of both computational and experimental approaches, usually in nominal 2D setups. The present study aims at evaluating 3D flow features in the wake of a idealized transverse dune, if any, under different nominal 2D setup conditions by means of computational simulations and to compare the obtained results with experimental measurements available in the literature. Abstract : Highlights: Sand dune aerodynamics investigated within a computational study. Simulation of different experimental setups. Comparison between computational results and experimental measurements. Emerging 3D coherent, mushroom-like flow structures in a nominally 2D setup. Some good practices in dune aerodynamics are recommended.